Respuesta :
14x² - x - 3 = 0
14x² - 7x + 6x - 3 = 0
-7x(-2x + 1) -3(-2x + 1) = 0
(-7x-3) & (-2x+1) = 0
Roots: -7x - 3 = 0
-7x = 3
x = -3/7
OR -2x + 1 = 0
-2x = -1
x = 1/2
In short, Your Roots would be 1/2 and -3/7
Hope this helps!
14x² - 7x + 6x - 3 = 0
-7x(-2x + 1) -3(-2x + 1) = 0
(-7x-3) & (-2x+1) = 0
Roots: -7x - 3 = 0
-7x = 3
x = -3/7
OR -2x + 1 = 0
-2x = -1
x = 1/2
In short, Your Roots would be 1/2 and -3/7
Hope this helps!
(7x+3)(2x-1)
you have to find the multiples of -3 that when added will give the middle term
you have to find the multiples of -3 that when added will give the middle term